Fabrication of PEGylated Fe@Bi2S3 nanocomposites for dual-mode imaging and synergistic thermoradiotherapy. (5th June 2018) - Li, Erdong; Cheng, Xiaju; Deng, Yaoyao; Zhu, Jing; Xu, Xiaoding; Saw, Phei Er; Gu, Hongwei; Ge, Cuicui; Pan, Yue
Abstract : Multifunctional magnetic nanocomposites are fabricated for synergistic thermoradiotherapy and simultaneously MRI/CT dual-mode imaging. Abstract : Nanocomposites for integrating imaging and therapy have attracted tremendous attention for biomedical applications. Herein, Fe@Bi2 S3 nanocomposites modified with polyethylene glycol (PEG) molecules are fabricated for synergistic thermoradiotherapy. For such nanocomposites, Bi2 S3 exhibits a strong absorbance in the near-infrared (NIR) region, which allows Bi2 S3 to convert energy from light into heat for effective photothermal therapy (PTT), whereas Bi can also significantly enhance radio-mediated cell death induction as a radiotherapy sensitizer due to its high atomic number (high-Z). Most importantly, it is found that the combination of PTT and radiation therapy (RT), using PEGylated Fe@Bi2 S3 nanocomposites, can bring a strong synergistic effect for the tumor treatment in in vitro and in vivo experiments. Besides, the magnetic Fe core and the Bi2 S3 shell components endow this nanocomposite with an ability to serve as both a magnetic resonance imaging (MRI) and computed tomography (CT) contrast agent. Therefore, our work presents a new type of multifunctional nanocomposite with the potential for synergistic thermoradiotherapy and simultaneously MRI/CT imaging.